Ecolabeling and the Greening of the Food Market - James J. Ferguson (EDIS)
This document is HS915, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January, 2003.